Efficacy of two primer sets used in Sex Identification of Rufous-winged Buzzard (Butastur liventer). - Paitoon Kaewhom; Kanokrat Srikijkasemwat (My University, 2021)
The rufous-winged buzzard (Butastur liventer) belongs to the order Accipitriformes, which is monomorphic, resulting in the difficulty to identify the gender. However, sex determination is important for predicting the sex ratio of this buzzard in nature in order to avoid its extinction.We aimed to develop a primer set that is able to sex the rufous-winged buzzard through polymerase chain reaction (PCR) amplification and compare the efficacy of the two sets of primers by using PCR technique.In the following, sensitivity refers to the smallest DNA concentration that allowed us to accurately sex a bird and specificity refers to the ability to clearly distinguish the sex based on the visual appearance of the bands. Blood samples were collected from captive buzzards. The DNA was extracted from them and was diluted to 50, 25, 10, 5, 2.5, 1.67, and 1 ng/μl. Two sets of primers, including P2/NP/MP and 2550F/2718R, were used to amplify the chromo-helicase DNA binding (CHD) gene of known gender buzzards using the PCR process to determine gender and to compare their sensitivity. To measure specificity, both primers were used to amplify CHD gene fragment of other unknown gender birds.The lowest concentration of the DNA template where P2/NP/MP could amplify DNA fragments was 1 ng/μl, and this set of primers could identify the gender of all birds correctly, giving 100% specificity. On the other hand, the 2550F/2718R could amplify the DNA fragments from 5 ng/μl, and it had only 78% specificity.The P2/NP/MP primer set was able to correctly identify the gender of rufous-winged buzzard through PCR amplification with high specificity and sensitivity.
Keywords: Buzzard; Primer (cosmetics); Identification and Quantification in Food